2018
DOI: 10.1161/jaha.117.007601
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of VEGF Mediated Flk‐1 Signaling Leads to a Gradual Loss of Vessel Health and Cardiac Function During Myocardial Infarction: Potential Therapy With Pellino‐1

Abstract: BackgroundThe present study demonstrates that the ubiquitin E3 ligase, Pellino‐1 (Peli1), is an important angiogenic molecule under the control of vascular endothelial growth factor (VEGF) receptor 2/Flk‐1. We have previously reported increased survivability of ischemic skin flap tissue by adenovirus carrying Peli1 (Ad‐Peli1) gene therapy in Flk‐1+/− mice.Methods and ResultsTwo separate experimental groups of mice were subjected to myocardial infarction (MI) followed by the immediate intramyocardial injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…6f). Peli1 is also reported to activate Akt [38,39], which is an important signaling in the regulation of neuropathic pain [40,41]. We found that knocking down Peli1 induced a significant reduction in Akt phosphorylation by 65.1% in the ipsilateral spinal cord, in comparison with scrambled shRNA control (Fig.…”
Section: Downregulation Of Peli1 Attenuates Cci-induced Mapk Phosphormentioning
confidence: 53%
“…6f). Peli1 is also reported to activate Akt [38,39], which is an important signaling in the regulation of neuropathic pain [40,41]. We found that knocking down Peli1 induced a significant reduction in Akt phosphorylation by 65.1% in the ipsilateral spinal cord, in comparison with scrambled shRNA control (Fig.…”
Section: Downregulation Of Peli1 Attenuates Cci-induced Mapk Phosphormentioning
confidence: 53%
“…As a downstream of vascular endothelial growth factor receptor 2 (VEGFR2), Pellino1 induces the AKT and MAPK activated protein kinase 2 (MK2) phosphorylation to restore cell migration potential, proangiogenic responses and the wound healing ability with VEGFR2 deficiency in vitro and in vivo (114). Further studies demonstrated that Pellino1 is a novel proangiogenic molecule directly regulated by VEGFR (115). In mouse ischemia models, Pellino1 deletion increases oxidative stress, reduces cIAP2-NF-kB cell survival, decreases angiogenic response, and lowers tissue function (116).…”
Section: Pellino Family In Tumor and Micrornas Related Signalings Pel...mentioning
confidence: 99%
“…It appears that acute myocardial infarction-induced reduction of Pellino-1, an important angiogenic molecule under the control of vascular endothelial growth factor (VEGF) receptor 2/Flk-1, leads to reduced activities of AKT and eNOS ( Thirunavukkarasu et al, 2018 ). Therefore, we examined whether sunitinib may also affect AKT and eNOS activities via Pellino-1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the intermediate molecules that link VEGF receptor and AKT is largely unknown. A recent study revealed that Pellino-1 is an important angiogenic molecule under the control of VEGFR2/Flk-1, as evident in that down regulated Pellino-1 expression during myocardial infarction contributes to suppression of VEGF-mediated angiogenesis via Pellino-1/AKT/eNOS pathway ( Thirunavukkarasu et al, 2018 ). In our experimental model, we found that application of sunitinib led to a significant decrease in the expression levels of Pellino-1 both in the rat artery tissue and in the primary cultured MAECs, suggesting that Pellino-1 may associate with sunitinib-induced decrease in ATK and eNOS activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation